2014
DOI: 10.1016/j.sbspro.2014.11.061
|View full text |Cite
|
Sign up to set email alerts
|

An International Comparison of the Determinants and Financial Information Quality in XBRL Reporting Environment

Abstract: The rapid development of technology had impacted the way businesses communicate information to the stakeholders. eXtensible Business Reporting Language (XBRL) offers the ability to exchange financial information globally through a digitalized global standard language. To reduce information asymmetry, most studies on XBRL were carried out emphasizing on the reasons for the new technology adoption and intention for implementation, but studies on XBRL implications or effectiveness are still scarce. Expected to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…On the other hand, it is found that the application of XBRL in business reporting certainly minimizes the administrative burden of both reporting organizations and regulatory authorities at large (Vasarhelyi et al, 2012). Technological advancement through XBRL for financial reporting influences the way companies share information with their stakeholders and allows financial data to be shared globally using a digitalized global standard language (Tarmidi and Roni, 2014). The advent of such technology has directly influenced the traditional mode of financial reporting and has contributed to a better transformation of financial reporting in a customized manner (Abeywardana et al, 2022).…”
Section: Influence Of Xbrl Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is found that the application of XBRL in business reporting certainly minimizes the administrative burden of both reporting organizations and regulatory authorities at large (Vasarhelyi et al, 2012). Technological advancement through XBRL for financial reporting influences the way companies share information with their stakeholders and allows financial data to be shared globally using a digitalized global standard language (Tarmidi and Roni, 2014). The advent of such technology has directly influenced the traditional mode of financial reporting and has contributed to a better transformation of financial reporting in a customized manner (Abeywardana et al, 2022).…”
Section: Influence Of Xbrl Technologymentioning
confidence: 99%
“…For instance, many earlier studies (Geiger et al, 2014;Mao and Zhang, 2019;Hoitash et al, 2021;Ilias et al, 2020;Cormier et al, 2022) studied the use of XBRL for financial reporting, but their focus was on its functioning, efficiency, taxonomy design, benefits and opportunities. Only a few studies conceptually focused on XBRL and its influence on financial reporting quality (Tarmidi and Roni, 2014;Al-Ramahi et al, 2021;Tawiah and Borgi, 2022). Therefore, the present study is unique among XBRL literature and tries to analyse the influence of XBRL and its functionality on various aspects of financial reporting and its quality at large.…”
Section: Introductionmentioning
confidence: 99%
“…To induce advanced technologies in the financial reporting process the adopting firms can bear additional costs and needs training for their employees who are involved in the process of preparation and presentation of financial statements Krisko (2017). Financial reporting quality is influenced by various dimensions that may be differing from one organization to another Tarmidi and Roni (2014). Financial reports prepared by using advanced technologies such as XBRL enhance the comparability and utility of information so communicated.…”
Section: Earlier Studies and Literature Gapmentioning
confidence: 99%
“…To induce advanced technologies in the nancial reporting process the adopting rms can bear additional costs and needs training for their employees who are involved in the process of preparation and presentation of nancial statements (Krisko, 2017). Financial reporting quality is in uenced by various dimensions that may be differing from one organization to another (Tarmidi et al, 2014). Financial reports prepared by using advanced technologies such as XBRL enhance the comparability and utility of information so communicated.…”
Section: Earlier Studies and Literature Gapmentioning
confidence: 99%